Peningkatan Keterampilan Proses Sains Dan Kreativitas Siswa Melalui Model Inkuiri Terbimbing - Wiwin Trisnawati; Sulistyono Sulistyono; Anna Fitri Hindriana (Edubiologica: Jurnal Penelitian Ilmu dan Pendidikan Biologi, 2019)
One of alternative way to improve science process skills and student creativity is by using guided inquiry learning model. Improvement science process skills research and student creativity in the excretion system material concept was carried out in  SMP Negeri 1 Cigandamekar. This research was carried out by quasi-experimental method. The research was conducted on the eighth grade students of junior high school. The research  used two classes, there are class VIIIA as control and VIIIB as experimental classes. In control class  the learning process is carried out by conventional methods namely lectures and information discussions. While in the learning experimental class using guided inquiry models with discussion learning methods.The result shows that studied with guided inquiry models is increasing value of 96 % from learning I to learning II. The students who studied using guided inquiry learning models have higher values of science process skills than the control classes that using conventional learning models. This is proved by the average value of N-Gain in the assessment of science process skills in the experimental class which is 0.35 while in the control class the value of N-Gain is 0.23. The average value of science process skills in the control class was 53,48 and in the experimental class the value was 64,33. There is increasing value of students' science process skills after learning with a guided inquiry model of 10.22% The average value of creativity in the control class was 62.96 and in the experimental class the value was 83.28. And there is increasing in the value of students' creativity with indicators of fluency, flexibility, elaboration and originality with a cumulative value of 24.39%. Student responses toward learning with guided inquiry models value was 32,06 and students was agreeKeywords: Science Process Skill; Creativity; Excretion; Guided Inquiry